2020
DOI: 10.1364/boe.397792
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of burn wounds in an in vivo porcine model using terahertz spectroscopy

Abstract: The accuracy of current burn triage techniques has remained between 50-70%. Accordingly, there is a significant clinical need for the quantitative and accurate assessment of partial-thickness burn injuries. Porcine skin represents the closest animal model to human skin, and is often used in surgical skin grafting procedures. In this study, we used a standardized in vivo porcine burn model to obtain terahertz (THz) point-spectroscopy measurements from burns with various severities. We then extracted two reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Previous porcine scald studies used a pseudo-scald device by wrapping a plastic film around a bottomless glass bottle that was filled with hot water to conform to the surface of the skin. [39] In addition to our prior reporting, [32] other groups have also observed that this model results in certain burn depth variability between the anatomical locations, as well as between the center and the edges of each burn. [39,40] This variability is because good contact between the skin and the heat source may be obstructed by skin surface heterogeneities and air pockets.…”
Section: Introductionsupporting
confidence: 69%
“…Previous porcine scald studies used a pseudo-scald device by wrapping a plastic film around a bottomless glass bottle that was filled with hot water to conform to the surface of the skin. [39] In addition to our prior reporting, [32] other groups have also observed that this model results in certain burn depth variability between the anatomical locations, as well as between the center and the edges of each burn. [39,40] This variability is because good contact between the skin and the heat source may be obstructed by skin surface heterogeneities and air pockets.…”
Section: Introductionsupporting
confidence: 69%
“…A linear combination of broadband THz reflectivity and spectral slope was correlated with the density of discrete scattering structures in the skin layers. Additionally, in an in vivo porcine pseudo-scald model, it was shown that a similar combination of THz hyperspectral parameters, i.e., the area under the reflectivity curve and the roll-off spectral slope, introduced as a novel THz Z -metric value, can differentiate between burn injuries with burn depth exceeding or below 350 m, as determined by vimentin immunohistochemistry 48 . The Z -metric was further optimized to differentiate burns into two categories: 1. depth of injury greater than 50 of the dermis thickness, and 2. depth of injury less than 50 of the dermis thickness 49 .…”
Section: Introductionmentioning
confidence: 99%
“…However, upon the infliction of a burn injury, physiological events, such as increased capillary permeability, increased hydrostatic pressure, and edema, occur and increase the water content 17 . Later THz studies, using in vivo rat models, showed that the THz spectra of burns had increased reflectivity 72 hours postburn, which was consistent with overall water content increase due to edema and correlated with the density of structures within the skin 11,12,16,18,19 .…”
Section: Introductionmentioning
confidence: 71%